2011
DOI: 10.1530/erc-11-0315
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of second primary malignancies in patients with neuroendocrine tumors of the digestive tract and pancreas

Abstract: An increased association between neuroendocrine tumors of the gastrointestinal tract and pancreas (GEP-NET) and other second primary malignancies has been suggested. We determined whether there is indeed an increased risk for second primary malignancies in GEP-NET patients compared with an age-and sex-matched control group of patients with identical malignancies. The series comprised 243 men and 216 women, diagnosed with a GEP-NET between 2000 and 2009 in a tertiary referral center. The timeline, before-at-aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 15 publications
5
33
2
1
Order By: Relevance
“…Furthermore, breast malignancies accounted for 14.3% of additional primaries. These observations are consistent with a recently published study of a Dutch cohort and likely reflect the trend toward increased cancer surveillance over the last two decades combined with the fact that breast, prostate, lung, and colon cancers are among the most common cancers diagnosed in the U.S (Kamp et al 2012). Nevertheless, exogenous mitogenic effects of secretory products from a primary tumor causing neoplastic transformation as well as common environmental exposures or behavioral risk factors among a large number of cancers must also be considered (Neugut & Robinson 1992, Modlin et al 2003.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, breast malignancies accounted for 14.3% of additional primaries. These observations are consistent with a recently published study of a Dutch cohort and likely reflect the trend toward increased cancer surveillance over the last two decades combined with the fact that breast, prostate, lung, and colon cancers are among the most common cancers diagnosed in the U.S (Kamp et al 2012). Nevertheless, exogenous mitogenic effects of secretory products from a primary tumor causing neoplastic transformation as well as common environmental exposures or behavioral risk factors among a large number of cancers must also be considered (Neugut & Robinson 1992, Modlin et al 2003.…”
Section: Discussionsupporting
confidence: 91%
“…In our series, almost one-third (29%) of patients with SICs had an associated metachronous primary tumor, a finding consistent with what other investigators have reported for carcinoid tumors in general. Most recently, Modlin et al used the SEER database to show that carcinoid tumors of all types were associated with other non-carcinoid tumors in 22.4% of patients; however, other studies have reported associations with rates varying from 13.7 to 40.7% (Berge & Linell 1976, Saha et al 1989, Marshall & Bodnarchuk 1993, Kamp et al 2012. In the majority of these studies, the most common site of additional malignancy was the gastrointestinal tract, a finding not entirely reproduced by our data.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…A number of reports have also demonstrated increased risk of additional malignancies occurring in the NET patient set [8,9,10,11,12,13,14], a factor which may add to the already challenging management of individuals with NET if coexistent. With the aforementioned relatively prolonged natural history of this tumour type, this presents a pertinent clinical consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of an increased risk for SI-NETs associated with FH of breast cancer deserves further discussion. A first-degree FH of breast cancer has already been associated with an increased risk for CRC [32], but not for SI-NETs. The rate of metachronous breast cancer has also been reported to be higher than expected in patients with a previous diagnosis of NETs [10].…”
Section: Discussionmentioning
confidence: 99%